(de) Construcción política, publicidad y (des) ocultamiento - Contreras Godoy, Juan Pablo (Re-presentaciones: Periodismo, comunicación y sociedad, 2006)
The parenthesis here above in the title pretend to mean the imperceptible border between consciousness and unconsciousness. According to this, the present article declares that create a theory or a doctrine suppose the establishment of all that seams to be important to reinforce it, but also suppose consciously/unconsciously, the concealment of some ideas that could deny, put on doubt, maybe put on disorder the theory or the doctrine pretended. To confirm this phenomenon, the author of this article presents some principal moments of the Western knowledge history and goes forward with a thesis by saying that the dialectic, principal matrix and method in such history, produces the concealment by supposing in its proper terms a fundament or a finality, a subsuming movement and a synthesis. Such concealment could be considered as a negation of the difference because the dialectic has as a target its finality or synthesis and in such terms the parts involved would be countless
Keywords: Deconstruction; Concealment; Spectacle